Redesigning the in-plant supply logistics: A case study. (May 2020) - Saez-Mas, Aida; Garcia-Sabater, Jose P.; Garcia-Sabater, Julio J.; Ruiz, Angel
Highlights: A redesign of an in-plant supply system to an automobile assembly line is addressed. A mathematical model simplification can bring to light relevant improvable areas. The model optimizes the transportation time and products and suppliers' allocation. The alternatives proposed lead to reductions of up to 30% in the distribution time. Abstract: This paper addresses the redesign of an industrial assembly facility's internal logistics. To this end, it proposes a mathematical formulation that optimizes the components and parts' flow to feed the different workstations of the production lines. This flow of components starts at the reception docks where suppliers' trucks arrive. Components unloaded from trucks are moved to one or several storage areas by means of adequate handling equipment. Finally, components are transported to demand point located along the assembly line when required. Numerical results produced by the mathematical formulation for the studied plant show that savings of almost 33% in the total distribution time might be achieved by a better assignment of suppliers to reception docks and parts to storage areas, and by adequately choosing the capacity of the material handling equipment.